Structural Divergence in Reproductive Agency: Unraveling the 'Matrilineal Buffer' Against Contraceptive Discontinuation in Indonesia Using Multi-Group SEM - Leonardo Simanjuntak; Cinthya Callathea; Desiree Montesinos; Firzan Dahlan (Open Access Indonesia Journal of Social Sciences, 2025)
Despite the historical success of Indonesia's family planning program, the contraceptive prevalence rate (CPR) has stagnated, driven largely by high rates of contraceptive discontinuation (29%). Conventional demographic analyses often attribute this to biomedical side effects, overlooking the structural influence of kinship systems and the potential confounding role of socioeconomic status. This study aims to analyze the structural pathways linking patriarchal gender norms to contraceptive discontinuation, mediated by reproductive autonomy, while explicitly controlling for educational attainment. We compare Indonesia’s two dominant cultural groups: the matrilineal Minangkabau and the patriarchal Javanese. A comparative cross-sectional study was conducted with 1,450 married women of reproductive age in West Sumatra (Minangkabau, n=725) and Central Java (Javanese, n=725). We employed Multi-Group Structural Equation Modeling (MG-SEM) with a rigorous invariance testing protocol. The model tested the "Patriarchal Norms → Reproductive Autonomy → Discontinuation Propensity" pathway, adjusting for age and education level. Measurement invariance (Configural and Metric) was established, allowing for valid group comparisons. The Minangkabau group exhibited significantly higher education levels (p<0.001). However, even after controlling for education, the structural analysis revealed a distinct divergence. Among Javanese women, patriarchal norms significantly suppressed autonomy (β = -0.58, p < 0.001), leading to higher discontinuation propensity. Conversely, Minangkabau women displayed a "Matrilineal Buffer"; the path from patriarchal norms to autonomy was non-significant (β = -0.09, p > 0.05), suggesting that cultural leverage protects decision-making power regardless of internalized gender norms. In conclusion, the mechanism of contraceptive discontinuation is culturally distinct. The "Matrilineal Buffer" is a robust structural phenomenon that persists independent of educational advantages. Interventions in patriarchal settings must dismantle barriers to female autonomy, while programs in matrilineal settings should focus on quality of care.